Enhancing phosphorus recovery from sewage sludge using anaerobic-based processes: Current status and perspectives. (December 2021) - Yu, Bohan; Xiao, Xiangmin; Wang, Jianwei; Hong, Meng; Deng, Chao; Li, Yu-You; Liu, Jianyong
Highlights: Nearly all of the P species can release via anaerobic-based processes. EPS and excessive metal ions are the two main limiting factors to P release. Acid fermentation & sulfate reduction are two promising processes for application. Anaerobic-based processes is economically feasible with simultaneous C, P recovery. LCA is required for synthetically evaluating wastewater treatment and P recovery. Abstract: Anaerobic-based processes are green and sustainable technologies for phosphorus (P) recovery from sewage sludges economically and are promising in practical application. However, the P release efficiency is always not satisfied. In this paper, the P release mechanisms (regarding to different P species) from sewage sludge using anaerobic-based processes are systematically summarized. The obstacles of P release and the updated achievements of enhancing P release from sewage sludges are analyzed and discussed. It can be concluded that different P species can release from sewage sludge via different anaerobic-based processes. Extracellular polymeric substances and excessive metal ions are the two main limiting factors to P release. Acid fermentation and anaerobic fermentation with sulfate reduction could be two promising ways, with P release efficiencies of up to 64% and 63%. Based on the summarization and discussion, perspectives on practical application of P recovery from sewage sludge using anaerobic-based processes are proposed.